THE USE OF VIDEO IN TEACHING WRITING PROCEDURAL TEXT:A Quasy-Experimental Study in One of Senior High Schools in Bandung - Alien Amalia, - (2012)
This study centered on the use of video in teaching writing procedural text. It was aimed to discover the effectiveness of video in teaching writing procedural text. Moreover, it examined how video could influence students' procedural text writing skill and their perceptions toward the learning. This study was conducted from the consideration that writing skill is difficult to acquire. Therefore, it is important for teachers to find out appropriate media in teaching writing text, including procedural text. A quasy-experimetal design was used in this study and the data were collected through pre-test, post-test, and interview to gain relevant data. The data were analyzed quantitatively using t-test SPSS version 17 for Windows, while the interviews were analyzed qualitatively. In selecting the samples, the tenth grade students of a senior high school in Bandung were selected. There were two classes as the samples; the first was the experimental group and the other was the control group. From the findings, it was shown that video is effective in improving students' procedural text writing skill. It is indicated by the results of t-test computation, the significant value of the post-test score was 0.021 < 0.05 (two-tailed). Furthermore, the effectiveness was also supported by the students' responses in the interview. Most of the students enjoyed writing using video. They felt that through watching video their writing skills improved. The improvements were in terms of vocabularies, comprehensions and ideas. This study recommends that teachers can use video as an alternative media in teaching writing procedural text. In addition, for further studies, it would be better if video is also used in teaching writing texts in different genre.